PENGARUH PEMBELAJARAN DARING TERHADAP KEMAMPUAN ANALISIS LAPORAN KEUANGAN PADA MAHASISWA AKUNTANSI UNIVERSITAS NEGERI SURABAYA - Nugrahani, Aulia Alin; Ahlunnaja, M. Zamrud (Jurnal Pijar, 2024)
This study aims to analyze the effect of online learning on the ability to analyze financial statements in Accounting students at Surabaya State University. Along with the development of educational technology, online learning is a method that is often used among universities. Therefore, this study tries to explore how online learning affects students' ability to master accounting concepts, especially in analyzing financial statements. This study uses a quantitative approach with quantitative descriptive design and test. The research sample was selected by purposive sampling by considering students who have taken the financial statement analysis course through online learning. Data were collected through a questionnaire consisting of two main parts: perception of online learning and ability in financial statement analysis.